The negative role of social media during the COVID-19 outbreak - Yas, Harith (International Information and Engineering Technology, 2021)
The outbreak of the COVID-19 pandemic has exposed the power of social media in the dissemination of information. The current pandemic has hurt not only social media users but also on state's sustainable development. As a result, the present study seeks to understand the reasons for using social media during the COVID 19 pandemic by screening various topics and assessing the impact of misinformation on social media, primarily psychological and mental effects. The study utilized a quantitative research design. Participants were individuals between the age of twenty and fifty. Data was collected using a questionnaire shared online to the 360 participants. The studies' responses were analyzed using descriptive statistics and the arithmetic percentage method using graphs and figures. The study results revealed that many respondents use social media as a source of information, news, and psychological nourishment. Besides, the results indicated that participants below 50 years of age used social media frequently. Whatsapp, Twitter, and Youtube were the most used social media sites among the participants. The findings indicated that most participants used social media as a source of vital information during the COVID-19 pandemic. The current study recommends that governments and health institutions focus on developing abilities to respond simultaneously to misinformation cases. This study has facilitated more knowledge into the uses of social media in times of health crises. The study acts as a blueprint to prepare the world for managing social media information sharing in the future.